The rhetorical constructions of global citizenship and the location of youth: A critical analysis (International Journal of Development Education and Global Learning, 2017)
The recent growth of global citizenship scholarship, especially in so-called Western universities, could entice us into making constructive assumptions about the viability of this area of study and teaching. Especially with respect to the lives of young people, the promise of global citizenship and its growing disciplinary popularity can be read as contributing to more connected and selectively realizable world communities, which share more of their lives' possibilities for the wellbeing of all. With this in mind, and with a continuing focus on the rhetorical claims of global citizenship – as opposed to the practical or even quasi-practical actualizations of such citizenship – and as a select thematic response to The National Youth White Paper on Global Citizenship (2015) produced by high school students in Canada, this paper attempts to expose the weaknesses that are ingrained in the scholarly constructions of the case. It also analyses the precarious global citizenship location of youth in both developed and developing world contexts. At the end, the paper suggests possible ways of educating for a more inclusive global citizenship, which values all knowledge systems and advances the wellbeing of diverse communities across the world.